(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: colonoscopy; abdominal pain; lower GI bleeding; mass lesion; therapeutic yield doi: 10.3329/jcmcta.v18i2.3833 Journal of Chittagong Medical College Teachers’ Association 2007: 18(2):28-31